Composition of fish assemblages in the southern part of the Main Outfall Drains, Southern Iraq - Abdul Hussein Jaafer Abdullah; Sajad Abdul Gani Abdullah; Ali Taha Yaseen (Caspian Journal of Environmental Sciences)
Fish assemblage was investigated in the southern part of the Main outfall drains, southern Iraq from January to December 2019. Monthly variations were recorded in water quality parameters including water temperature, dissolved oxygen, salinity, electric conductivity, turbidity, hydrogen ion, and total dissolved solids. A total of 10981fish specimens belonging to 27 fish species, 25 genera, 17 families, and eight orders were collected from the southern part of the Main outfall drains. Marine fish species were 19 and eight species from freshwater. Three species were presiding the numerical relative abundance of species formed 80.96% of the total number of species. In this region, Acetrogobius dayi represented 32.00%, Boleophthalmus dussumieri 28.92% and Aphanius dispar 20.04% of the total number of species. The status of ecological indices were poor for diversity index (H), richness index (D) was troubled, and semi-balanced for evenness index (J). The present study showed bad water quality after analyses of physicochemical variables, and also sensory indicators (colour and smell) of the water which play a major role in the blending composition of the fish community structure. The results revealed that salinity has a large contributor to determine the nature spread and distribution of the fish populations. The study exhibited that the river habitat is unstable, affected by three factors: 1) Quantity and quality of freshwater coming from Al-Siphone regulator in Thi-Qar Province; 2) The tidal process spread organic pollution that are dumped in Hamdan region, Southern Basrah City; and 3) The chemical and organic pollutions resulting from reclamation of agricultural lands.